Titrating the neuroplastic effects of cathodal transcranial direct current stimulation (tDCS) over the primary motor cortex. (October 2019) - Mosayebi Samani, Mohsen; Agboada, Desmond; Jamil, Asif; Kuo, Min-Fang; Nitsche, Michael A.
Abstract: Transcranial direct current stimulation (tDCS) non-invasively induces polarity-dependent excitability alterations in the human motor cortex lasting for more than an hour after stimulation. Clinical applications with encouraging results have been reported in several pilot studies, but the optimal stimulation protocols remain to be determined. This is also important because the efficacy and directionality of tDCS effects follow non-linear rules regarding neuroplastic effects for the stimulation parameters duration and intensity. In this study, we systemically explored the association between tDCS, these parameters and induced after-effects on motor cortex excitability. Cathodal tDCS was applied in four different intensities (sham, 1, 2 and 3 mA) and three durations (15, 20 and 30 mins) in 16 young healthy subjects and the after-effects were monitored with TMS-induced motor evoked potentials (MEP) until the next day evening after stimulation. The results of the repeated measures ANOVA conducted to disentangle the effects of tDCS intensity and duration show a main effect of intensity in which 1 mA and 3 mA stimulation induced a reduction of MEP amplitudes, but 2 mA resulted in excitability enhancement. The results of a secondary ANOVA conducted to compare if active stimulation effects differ from those of sham stimulation revealed a significant main effect of tDCS condition in which 1 mA–15 min, 1 mA–30 min and 3 mA–20 min cathodal tDCS induced LTD-like plasticity, while LTP-like plasticity was observed after 2 mA–20 min stimulation. Our study thus provides further insights on the dependency of tDCS -induced neuroplasticity from the stimulation parameters, and therefore delivers crucial information for future applications.